Assessing the role of citizenship education provision in preventing extremist radicalisation - Gaffney, Francis (Cranfield University, 2018)
Radicalisation towards violent extremism within educational settings has emerged as a high profile and critical issue in many contemporary societies. Debates around the appropriate role of educational institutions should play in this regard have attracted intense media and public debate both in the UK and internationally. Arguably, education should be at the heart of anti-, -radicalisation plans, with an emphasis placed on educating children in a way that improves their economic, social, and personal well-being by developing resiliency. This research involved face-to-face interviews with 51 education sector professionals to establish an evidence base regarding current practice regarding the understanding of radicalisation and building young people’s resilience to violent extremism. These professionals were based across ten countries in Europe and the Middle East. This research aimed to examine staff attitudes to different aspects of the National Curriculum, notably Personal, Social, and Health Education (PSHE) and Citizenship Education (CE), aand how these could potentially impact on, or act as a source of potential triggers for, radicalisation. Several major themes were identified in the interview responses. In particular, the results highlighted a range of the limitations and shortfalls perceived by staff in CE provision and delivery. Many of these were widely shared across the sector while a few were more specific to certain regions. Major themes included 1) failings with how CE was delivered; 2) the impact of limited time allocation on CE activity; 3) a wide range of other challenges with regard to CE implementation; and 4) staff apprehension regarding their role and the role CE potentially plays in countering extremist behaviour. Regional level differences included, for example, participants in the UK flagging concerns about giving offence, participants in other European countries highlighting immigration and far-right issues, and participants in the Middle East heavily focusing on the 2011 Arab Spring and Sunni-Shi’a tensions. The results are compared with past research in this area and are used to identify a series of policy and practice recommendations, as well as avenues for future research